До феноменологічної теорії лавиноподібного ефекту в мікрохвильовій нелінійній ВТНП лінії передачі з постійним струмом - Melnyk, S. I.; Melnyk, S. S.; Lavrinovich, A. A.; Cherpak, M. T. (Publishing house "Academperiodika", 2019)
A phenomenological model has been proposed to describe the avalanche-like transition of a microwave nonlinear HTSC-based transmission line into a dissipative state. This effect was observed by the authors in a dc-biased transmission line. The proposed model generalizes the well-known phenomenological model for the nonlinear HTSC-based transmission line under the action of a direct current. The character of the dependences obtained for microwave losses allows the jump-like changes in the properties of the nonlinear HTSC-based transmission line to be regarded as a fold-type catastrophe and the methodological and mathematical apparatus of the theory of catastrophes to be used in order to explain the results obtained and predict new ones.